Use of deproteinised leaf juice of Medicago sativa L. for the production of α-amylase (Journal of Bio-Science, 2019)
Leaf protein concentration (LPC) is a good source of cyanocobalamine (B12), ascorbic acid (vitamin C) and folic acid (vitamin B9). After isolation of LPC from leaves the remaining by product is deproteinised leaf juice (DPJ) which is rich in water soluble carbohydrates, free amino acids, minerals, lipids and vitamins. The dry matter (DM) and nutrient composition of DPJ varies from species to species. The DM content in this fraction was found between 1.2 to 4.0%. Six fungi were grown on the DPJ expressed from Medicago sativa, Anethum graveolens, Spinacia oleracea, Trigonella foenium-graecum, Coriandrum sativum and also on conventional GN medium to evaluate the suitability of DPJ as a medium for fungal growth and subsequent production of ∝-amylase. The efficiency of DPJ as a medium for fungal growth was evaluated and its value in microbial biotechnology for the production of ∝-amylase was tested. Increase in concentrate of flour in the DPJ there was simultaneous increase in the mycelial dry weight (MDW) production of the six fungi under investigation. On DPJ alone, the yield of MDW was between 76.0 and 89.5 mg which increased to 164.5, 131.0 and 117.0 mg respectively under the influence of the flours of wheat, sorghum and maize respectively. Maximum response to the enrichment of DPJ by flour was noticed with A. niger. As with the increase in growth of fungi with increasing concentration of flour, the activity of amylase also increased. On an average it was 34 - 96 U/ml when the fungi were grown on DPJ alone, which increased to 301, 265 and 276 U/ml under the influence of flours.J. bio-sci. 26: 07-14, 2018